Understanding Microalgae Behavior Under Alternating Energy Starvation and N-starvation Conditions to Develop “feast-and-famine” Processes - Fabrizio Di Caprio; Francesca Pagnanelli; Pietro Altimari (Chemical Engineering Transactions)
Feeding organic substrates to microalgae cultures in photo-heterotrophic, mixotrophic, or fully heterotrophic processes could provide effective solutions for enhancing the economic and environmental sustainability of industrial microalgae cultivation, particularly when wastewaters or agro-industrial by-products are used as organic substrate sources. However, controlling bacterial contamination remains a major challenge that hinders the scalability of such processes. The application of feast and famine strategies has been shown to mitigate contamination issues. Nevertheless, comprehensive kinetic models that can predict microalgal behavior under variable nutrient stress conditions are lacking. This study aims to provide a preliminary understanding of microalgae behavior under different combinations of energy and nitrogen starvation conditions. The objective is not only to understand the responses to specific starvation conditions but also to examine how behavior changes depending on the previous environmental conditions of the inoculum. In this paper, various combinations of nutrient availability conditions were tested on a strain of Chlorella sorokiniana. Under heterotrophic nitrogen starvation, microalgae growth followed a logistic model, with a fattening factor of 2.8 and a maximum specific growth rate (µmax) of 0.032 h?¹. Under energy starvation conditions, with or without nitrogen, on average 16% biomass reduction was consistently observed within 48 hours, with no significant effect from prior nutrient conditions. Cell concentration exhibited different behaviors, with cell numbers increasing under most energy starvation conditions, except when microalgae were transferred from nitrogen starvation to simultaneous nitrogen and energy starvation. Conventional first-order models were inadequate to describe biomass decay under energy starvation conditions. Therefore, kinetic models that account for the consumption of intracellular components, such as carbohydrates, should be developed. The results of this study provide insights that can be used to develop innovative models to predict microalgae behavior under variable nutrient availability conditions. These insights allow the development of new cultivation processes more environmentally sustainable than the conventional ones.